O papel das florestas preservadas contra os efeitos dos agrotóxicos e da radiação solar ultravioleta em girinos e o potencial de pequenas propriedades rurais na redução de impactos - Rocha, Marcelo Carvalho da (2020)
Amphibians are the most threatened group of vertebrates on the planet, declines have already been observed in natural populations in various regions of the globe. Several hypotheses have been proposed to elucidate this, including increased exposure to solar ultraviolet (UV) radiation and pesticides. The Atlantic Forest has one of the highest concentrations of amphibian biodiversity on Earth. However, the intensive increase in agricultural activities, often without respect for the Brazilian forest code, especially with regard to maintaining the width of riparian forests, puts at risk the biodiversity dependent on these ecosystems. Therefore, in this study, we evaluated how the lack of forests in agricultural landscapes influences the amount of pesticides in the water, as well as the incidence of solar UV radiation. Second, we evaluate the impact of the reduction of riparian forest caused by agricultural activities on the density of tadpoles and on the increase in chromosomal damage of two species of amphibian specialists in forests. The protection provided by a well-preserved riparian forest, with a dense cover, blocks the incidence of solar UV radiation and the influx of pesticides into streams. Consequently, preserved streams have a greater abundance of tadpoles and less chromosomal damage than environments without riparian forest. This study clearly demonstrates that the preservation of the continuous riparian forest, in accordance with the law, is effective in reducing the decline of threatened amphibians. However, maintaining these preserved areas increases the cost of production, especially for family-based rural properties, which end up having financial sustainability problems or, simply, do not comply with the legislation. Having knowledge of this paradigm, in this study we aim, in addition to pointing out what generates the loss of biodiversity based on the data collected in the field, to propose the creation of a program. This program focuses on reducing negative impacts, especially with the reduction of riparian forest in small streams, due to rural activities, on small agricultural properties. To this end, we outline tools that protect the natural landscape and wildlife, and also consider the need for rural sustainability. The program called Nature-Friendly Property covers a range of projects certified by local labels, which allow extra income on properties that voluntarily adhere to the proposal, using ecotourism with a focus on an audience that seeks authentic experiences, focused on traditional practices enriched by contact with the local population. The properties will have technical support to comply with environmental laws that protect the riparian forest, springs and legal reserve, through projects for the recovery of degraded areas, thus having an extra income alternative to compensate the areas that will be preserved. A payment for environmental service is also planned, for owners who wish to preserve beyond what the law provides. The program has already been approved by the advisory council of the Parque Estadual do Turvo and a working group is already mobilized for its implementation on a rural property that will be the model property. In this perspective, we align national agriculture with international sustainability initiatives that work at the intersection of business, agriculture, forests and biodiversity conservation.